PENANGANAN KONFLIK INTERN UMAT ISLAM DAN IMPLIKASINYA TERHADAP KETAHANAN SOSIAL KEAGAMAAN (Studi di Perumahan Villa Mutiara Gading 2 Kab. Bekasi Jawa Barat) - , Priya Jarkasih ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Islam is a religion which embrace the majority of the population in Indonesia. As a religion embraced by many residents. Islam certainly has an important role in the course of the nation. However, Islam also has its own pluralism, both on the characteristics of doctrine, race and religious symbols. This study aims to determine what factors are the potential conflicts that exist within the Islamic Internal faith housing communities Villa Mutiara Gading 2 Bekasi, knowing the background of social interaction and community, analyze the role of the characters in conflict and to find coping strategies to resolve conflicts within the community housing. The research method used was qualitative research using observations and observations involved approach in order to give emphasis on the nature of social reality. The research was conducted in Housing Villa Mutiara Gading 2 Bekasi. Determination of interview conducted using a random method. Respondens in this study were residents Villa Mutiara Gading with 40 head of household respondents Islamic community housing Villa Mutiara Gading 2 Bekasi. The results showed that: Causes of conflict among Muslims that occurred in housing is the difference in beliefs, values, and competition triggered by the elites and discrimination against certain groups. Treatment efforts have been made in overcoming the internal conflicts in the religion housing of the Islamic ummah is not optimal and is impacting on the resilience of religious social housing of community.